Efektivitas Penerapan Undang-Undang Nomor 7 Tahun 2017 dalam Pengawasan Politik Uang pada Pilkades di Desa Penawangan Kabupaten Grobogan - Mutiara Warda Mulyani; Hananto Widodo (MLJ Merdeka Law Journal, 2025)
This study aims to analyze the effectiveness of the implementation of Law Number 7 of 2017 concerning the supervision of money politics practices in the 2020 Village Head Election  in Penawangan Village, Grobogan Regency. This research is based on the rampant practice of money politics in the Pilkades process, which fundamentally violates the principles of honesty, fairness, and transparency. The research method used was empirical juridical, involving interviews with the Head of the Village Consultative Body in Penawangan Village. The results indicate that money politics remains a primary strategy for attracting public participation, primarily due to low citizen interest in voting without material rewards. Village head candidates generally utilize economic approaches and political marketing tricks by offering money or assistance to residents to garner sympathy and support. All candidates employ similar strategies, but strive to minimize costs through the role of their respective campaign teams. The Village Consultative Body and the Penawangan District conducted strict oversight and a comprehensive evaluation of the village head election  process. Overall, this study concludes that the implementation of Law No. 7 of 2017 on money politics in Penawangan Village has not been fully effective, due to weak public legal awareness and the existence of economic rationalization in local politics. Nevertheless, the oversight and outreach efforts undertaken by the village and sub-district are important steps in building a more honest and democratic political consciousness in the future.